2010
DOI: 10.1002/chem.201001827
|View full text |Cite
|
Sign up to set email alerts
|

High‐Temperature Stable, Iron‐Based Core–Shell Catalysts for Ammonia Decomposition

Abstract: High-temperature, stable core-shell catalysts for ammonia decomposition have been synthesized. The highly active catalysts, which were found to be also excellent model systems for fundamental studies, are based on α-Fe(2)O(3) nanoparticles coated by porous silica shells. In a bottom-up approach, hematite nanoparticles were firstly obtained from the hydrothermal reaction of ferric chlorides, L-lysine, and water with adjustable average sizes of 35, 47, and 75 nm. Secondly, particles of each size could be coated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 23 publications
3
86
0
1
Order By: Relevance
“…The US Department of Energy has clearly indicated that the feasibility of ammonia as hydrogen storage molecule relies on its decomposition at temperatures aligned with those of the PEM fuel cell, in the range of 150-180°C making necessary the development of catalysts active under these conditions [18]. To date, the most effective catalyst for ammonia decomposition consists of ruthenium particles supported on carbon nanotubes (CNT) due to their high conductivity (6353 mol H 2 mol…”
Section: Hydrogen Production Via Ammonia Decompositionmentioning
confidence: 99%
See 2 more Smart Citations
“…The US Department of Energy has clearly indicated that the feasibility of ammonia as hydrogen storage molecule relies on its decomposition at temperatures aligned with those of the PEM fuel cell, in the range of 150-180°C making necessary the development of catalysts active under these conditions [18]. To date, the most effective catalyst for ammonia decomposition consists of ruthenium particles supported on carbon nanotubes (CNT) due to their high conductivity (6353 mol H 2 mol…”
Section: Hydrogen Production Via Ammonia Decompositionmentioning
confidence: 99%
“…In this context, it is important to note that the most popular commercial catalysts for the large-scale production of ammonia are based on iron promoted with K 2 O, CaO, SiO 2 , and Al 2 O 3 , active at temperatures above 400°C [29]. While most of the fundamental research regarding catalyst development for ammonia decomposition is on rutheniumbased systems, the bulk price of iron is 50,000 times lower than that of ruthenium, giving rise to an obvious significant cost benefit associated to the development of effective ironbased catalysts with similar activity than ruthenium ones [18]. The relatively lower activity of iron with respect to ruthenium-based catalysts can be explained by the stronger bond enthalpy of Fe-N compared to Ru-N which can lead to the formation of surface nitrides which slows down the reaction rate and eventually deactivates the catalysts by poisoning.…”
Section: Iron-based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 A common route of synthesis for Janus particles is using electrostatic assembly 18−23 and spontaneous formations. [6][7][8][9][10]24 This method is frequently used to make hierarchical templates that can then be selectively coated to make asymmetric colloidal structures. 18−23 Such templates are usually synthesized by mixing in the same solution a core particle of one charge and satellites of the opposite charge.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, welldispersed palladium nanoparticles in mesoporous SBA-15 were also prepared with sol-gel route, and the resulting nanocomposites exhibit a highly catalytic activity and reused ability for both the Suzuki and Heck coupling reactions [17]. Moreover, core-shell structure materials had also been prepared for the sake of enhancing the catalytic stability [18,19]. Recently, Opanasenko provided an outstanding overview on the heterogeneous Pd catalysts [20].…”
Section: Introductionmentioning
confidence: 99%